Implications of vector change in electrochemical jet processing. (January 2021) - Bisterov, Ivan; Speidel, Alistair; Mitchell-Smith, Jonathon; Clare, Adam T.
Abstract: Curved toolpaths challenge accurate electrochemical jet processing due to resulting distortion of the cut profile. A more elaborate path planning approach is required to mitigate these negative effects. A 3-dimensional process model is presented here,  to predict the resulting surface geometry. This is applied to simulate machining of curved channels and calculate optimised feed rates for locations of the toolpath with impaired geometry. Through the presented predictive planning methodology, achieved depths of curved sections of the machined channels were within 10.5% of the depth for straight sections, compared to up to 62.2% increase when feed rate compensation was not applied.